Influence of Strategic Change on Employee Performance Case of Hotels in Western Kenya Circuit - Florence Auma , Odera; Charles, Ondoro (International Journal of Scientific Research and Management (IJSRM), 2023)
The hotel industry is one of the fastest growing sectors of the global economies; its significant contribution is seen to be on an upward trend, as evidenced here in Kenya where international hotel chains are opening its branches within developed towns to reap the market rewards from this competitive industry. The current rapid growth in hospitality industry has triggered stiff competition which requires exemplary service to be able to attract and maintain loyal customers during any tourist season. Thus, interest to the Western Kenya Circuit which is still virgin in nature and development. This study aimed at determining the influence of strategic change organizational mission on employee performance, case of hotels in western Kenya circuit. The study adopted Lewin’s model and Contingency theories of change on theoretical framework. A correlation survey was adopted to conduct research where questionnaires were used to collect primary data while secondary data sourced from relevant reviewed literature. The study assessed hotels in Western Kenya circuit. The study population was 585 employees from different levels working in the hotels. Total of 116 were selected as the sample size using stratified random sampling procedure with different level of employees forming basis of strata. Data was tested for validity via exposure to experts and reliability by Cronbach’s Alpha test on pilot data from 12 respondents. Reliability results indicated all three scales reliable at .801, .777 and .825 a change in organization mission (β=.415>0.05). A statistical model with the two as independent variables accounted for 26.1% of variation in employee performance (Adjusted R-Squared = 0.261>0.05). The study found that altering organizational culture didn't significantly impact employee performance, whereas changing the mission led to improved employee and organizational performance. A shift in mission enhanced feedback, efficiency, productivity, and competency. Western Kenya Circuit Hotels' employees value mission changes, showing greater motivation and effort when the purpose evolves. The implication of this finding was any efforts towards enhancing employee performance should focus primarily on aspects of hotels mission that are equally important to employee for overall performance. While acknowledging the importance of organizational change on performance, managers and stakeholders should reorganize the significance of each aspect of organization strategic change on mission in influencing employee performance and that of the organization.